2013
DOI: 10.1038/srep02071
|View full text |Cite
|
Sign up to set email alerts
|

Computational microscopy of cyclodextrin mediated cholesterol extraction from lipid model membranes

Abstract: Beta-cyclodextrins (β-CDs) can form inclusion complexes with cholesterol, and are commonly used to manipulate cholesterol levels of biomembranes. In this work, we have used multiscale molecular dynamics simulations to provide a detailed view on the interaction between β-CDs and lipid model membranes. We show that cholesterol can be extracted efficiently upon adsorption of β-CD dimers at the membrane/water interface. However, extraction is only observed to occur spontaneously in membranes with high cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 35 publications
(47 reference statements)
5
119
0
Order By: Relevance
“…Such an observed extraction phenomenon has been described to depend on the cell surface distribution of the CDs at least for the cholesterol whose membrane extraction is preferentially achieved by β-CDs [28][29][30]. This suggests a passive diffusion of the CDs into the lipid bilayer by directing their opened secondary rim towards the lipidic polar groups while remaining anchored to the glycerol-ester groups and phosphate by hydrogen bond formation.…”
Section: Direct Action Of the Cds On Cell Membranesmentioning
confidence: 96%
See 1 more Smart Citation
“…Such an observed extraction phenomenon has been described to depend on the cell surface distribution of the CDs at least for the cholesterol whose membrane extraction is preferentially achieved by β-CDs [28][29][30]. This suggests a passive diffusion of the CDs into the lipid bilayer by directing their opened secondary rim towards the lipidic polar groups while remaining anchored to the glycerol-ester groups and phosphate by hydrogen bond formation.…”
Section: Direct Action Of the Cds On Cell Membranesmentioning
confidence: 96%
“…Phospholipids, acting as acetylcholine precursor, would counteract the loss of cholinergic neurons responsible for impaired cognition in AD patients. The chitosan/phospholipid/β-CD microspheres were tested in vivo in rats modeling AD following Aβ [25][26][27][28][29][30][31][32][33][34][35] injection into the hippocampus. In these animals, learning and memory were improved according to Morris water maze test data compared to untreated littermates.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Savolainen et al studied toxicity/irritation caused by CDs on human corneal epithelial cell lines and observed that the cytotoxic effect was in the order of αCD > dimethyl-βCD > SBEβCD = HPβCD > γCD (9). In another study, Lopez et al performed a computational simulation of CDs interacting with cholesterol (8). It was reported that within 10 ns of the initial interaction, CDs orient in a perpendicular direction to the surface of the phospholipid monolayer and the hydroxyl groups of membrane cholesterol penetrate into the inner core of the CD.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, cholesterol is more abundantly present in plasma membrane, common recycling endosome and trans-Golgi complex [117]. Removal of cholesterol from these membranes, requires high concentrations (5-10 mM) and prolonged times because βCDs, which have an ~8 Ǻ deep cavity, must form stacked dimers (improbable event) to remove 18 Ǻ long cholesterols out of the lipid bilayer and shelter them from the water [118].…”
Section: Beta-cyclodextrins (β-Cds)mentioning
confidence: 99%
“…In normal cells, cholesterol is more abundantly present in plasma membrane, common recycling endosome and trans-Golgi complex [117]. Removal of cholesterol from these membranes, requires high concentrations (5-10 mM) and prolonged times because βCDs, which have an ~8 Ǻ deep cavity, must form stacked dimers (improbable event) to remove 18 Ǻ long cholesterols out of the lipid bilayer and shelter them from the water [118].In cells with Niemann Pick Type-C defect, i.e., with inactivating mutations in either NPC1 or NPC2 genes, that code for two intra-lysosomal lipid transporter proteins, cholesterol is, also, aberrantly accumulated within lysosomes. Removal of lysosomal cholesterol buildups requires lower concentrations (0.1-1.0 mM) and shorter incubation times with βCD [119].…”
mentioning
confidence: 99%